Aggressive statin therapy in acute coronary syndrome: therapeutic potential of atorvastatin in the daily dose of 80 mg - A. N. Britov (Кардиоваскулярная терапия и профилактика, 2009)
The paper reviews recent studies justifying high-dose statin therapy (in particular, atorvastatin treatment) in patients with coronary heart disease (CHD) and high risk of life-threatening coronary events. In the latest placebo- controlled and comparative studies of high statin doses (e.g., 80 mg/d of atorvastatin) in stable CHD or acute coronary syndrome (ACS), a dose-depended effect of statins has been demonstrated, especially during the first months after ACS and myocardial infarction.